Chinese medicine Tongxinluo capsule alleviates cerebral microcirculatory disturbances in ischemic stroke by modulating vascular endothelial function and inhibiting leukocyte–endothelial cell interactions in mice: A two‐photon laser scanning microscopy study. (9th February 2018) - Liu, Shen; Wei, Cong; Kang, Ning; He, Qilong; Liang, Junqing; Wang, Hongtao; Chang, Liping; Chen, Daohong; Zhang, Qiuyan; Chang, Chengcheng; Zhang, Junfang; Ren, Hong; et al.
Abstract: Objective: The aim of this study was to examine the effect of TXL, a Chinese medicine prescription, on cerebral microcirculatory disturbances after pMCAO in mice using TPLSM and further explore the underlying mechanisms. Methods: Adlut male C57BL/6J mice were subjected to pMCAO and orally administered with TXL (3.0, 1.5 and 0.75 g/kg/d) at 1, 3, and 21 hours after pMCAO. The following parameters were examined at 6 and 24 hours after pMCAO: neurological deficits, infarct volume, BBB permeability, cerebral microvessel structure, brain microcirculation (TPLSM imaging), vasoactive factors, and adhesion molecules. Results: TXL improved neurological deficits, reduced infarct volume, attenuated BBB disruption, protected cerebral microvessel structure, increased cerebral capillary flow velocity and volume flux, and inhibited leukocyte–endothelial cell interactions at 6 or 24 hours after pMCAO. The therapeutic efficacy was exerted in a dose‐dependent manner. Further study revealed that TXL (high dose) regulated the expression of PGI2, TXA2, and ET‐1, and suppressed ICAM‐1 and P‐selectin. Conclusions: TXL alleviates cerebral microcirculatory disturbances against ischemic injury by modulating endothelial function and inhibiting leukocyte–endothelial cell interactions. These effects are associated with regulating the expression of PGI2, TXA2, and ET‐1, and suppressing ICAM‐1 and P‐selectin expression.